A Study of Lipid Profile and Estradiol for Evaluation of Cardiovascular Risk in Pre- and Post-Menopausal Women - Prajakta Warjukar1 , Rakesh Kumar Jha2 , Prakash Kute3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Following menopause, decreased oestrogen production from ovaries leads to lipoproteinprofile derangement, drastic alterations in the metabolism of glucose and insulin, distribution of body fat,coagulation and fibrinolysis and vascular endothelium dysfunction. Oestrogens include many cardioprotectivemechanisms that alter the vascular tone by enhancing the levels of nitrous oxide. Endothelial cells arestabilized by oestrogens, they augment antioxidant potential and alter fibrinolytic proteins. These are allcardio-protective mechanisms that are reduced with beginning of menopause.Objectives: To evaluate the relation of oestradiol hormonal variation with plasma lipid concentrations inpre- and post- menopausal women.Material and Method: 50 premenopausal women and 50 postmenopausal female were selected as subjects.Data were obtained via clinical assessment from laboratory investigations and questionnai.Results: Serum levels of Total Cholesterol (TC), Triglycerides (TG), LDL-cholesterol, and VLDLcholesterol in postmenopausal women were significantly elevated when matched with premenopausalwomen. For postmenopausal women, the level of HDL-cholesterol declined substantially. The concentrationof estradiol in post-menopause women was significantly lower (p<0.001).Conclusion: Menopause results in alterations in the lipid profile by reducing HDL and increasing totalcholesterol (TC), triglycerides (TG), LDL-cholesterol and VLDL-cholesterol, thus raising the chancesof cardiovascular disease. These shifts are due to decreased amounts of oestrogen that are observed inmenopause.